PERAN WORLD WIDE FUND FOR NATURE (WWF) DALAM MENGEMBANGKAN EKOWISATA DI SUAKA MARGASATWA BUKIT RIMBANG BUKIT BALING - Herman, Fauzi; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research analyzes the role of World Wide Fund for Nature (WWF) to protect Bukit Rimbang Bukit Baling wildlife reserve in Kampar Kiri, Riau during 2012 until 2015. Bukit Rimbang Bukit Baling is well known with its biodiversity. It has been a destination of ecotourism for domestic and foreign tourist in the world. But, because of deforestation and illegal logging, so many plants and animals lost their environment there. It’s be serious problems that need to be solved as soon as possible.WWF is one of the non-governmental international organizations that focus to protect the environmental sustainibility. WWF has been doing positive roles in Indonesia since its formal formation in 1962. In realizing its goal to protect Bukit Rimbang Bukit Baling, WWF do several activities there such as ecotourism development, environmental education study, planting development, bioprospection activity, animal inventaritation, and others. WWF is also supported by other international organizations, local organizations, and government in every level.The datas were collected from many sources like books, journals, and websites that can support this research. In this research, the reseacher uses constructivism perspective to describe the role of WWF in Bukit Rimbang Bukit Baling. This research is also supported by international organization theories especially the theories that describe the role of international organization.Keywords : WWF, Bukit Rimbang Bukit Baling, ecotourism, biodiversity protection, international organization